Exploring the concept of “desistance” and age graded theory of informal social control by Sampson and Laub - Mohd Alif Jasni,; Nazirah Hassan,; Fauziah Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
“Desistance” is a criminological concept that discusses a person’s dismissal from criminal behaviour. The ambiguity of this concept leads to confusion about what words to use: stop, cease, evade or distance from crime. There is even no translation of this concept into the Malay language, which can cause problems, especially when discussing the study of re-offending. Thus, comprehensive research is required to scrutinise the causes of success in stopping or abstaining from crime in a group of former prisoners. This concept paper addresses the questions that arise and summarises the definitions made in previous studies while using the secondary study methodology to underpin this entire study. Also, it includes the Age Graded Theory by Sampson and Laub (1993) because this theory discusses how a person can successfully stop committing crimes through informal social control. This paper also discusses the critical components of this theory in detail, such as crime trajectories, life transitions, and turning points. This study concludes with the strengths and weaknesses of the theory concerning the discussion of the success of a former prisoner in avoiding crime.